Ответы и объяснения

2013-11-29T07:16:51+00:00
1.1)10 ^{-2x+3}= 10^{1}
-2x+3=1
2x=2
x=1
2) 3^{2x} -7* 3^{x} -18=0
Сделаем замену t= 3^{x} >0
 t^{2}-7t-18=0
По теореме Виета
 t_{1} =9
 t_{2} =-2  не является корнем, тк t>0
3^{x}=9
 3^{x}= 3^{2}
x=2
2. (\frac{6}{5})^x< \frac{5}{6}
 (\frac{6}{5}) ^x<( \frac{6}{5}) ^{-1}
тк  \frac{6}{5}>1 ,  то
x>-1
3. \left \{ {{x=-2-y} \atop { 6^{-2-y+5y} = 6^{2} }} \right.
 \left \{ {{x=-2-y} \atop {4y-2=2}} \right.
 \left \{ {{x=-2-y} \atop {4y=4}} \right.
 \left \{ {{x=-2-y} \atop {y=1}} \right.
 \left \{ {{y=1} \atop {x=-3}} \right.
4.1) 3^{ \frac{1}{3}(x+6) } > 3^{-2}
тк основание > 1, то 
 \frac{1}{3}(x+6) >-2
 \frac{x}{3}+2>-2
 \frac{x}{3}>-4
x>-12
2) (\frac{9}{7}) ^{ x^{2} -4}   \leq  (\frac{9}{7}) ^{0}
тк основание  \frac{9}{7}>1 , то
 x^{2} -4 \leq 0
(x-2)(x+2) \leq 0
-2 \leq x \leq 2